Perencanaan Strategis SI Menggunakan Metode Ward & Peppard pada PT Pulau Subur - Ishak, Reven Rudy; Pratama, Dicky (Universitas Multi Data Palembang, 2025)
The strategic plan of information systems at PT Pulau Subur aims to improve operational efficiency and competitiveness of the company in the palm oil plantation sector. In facing the challenges of rapid development of information technology, the company realizes the need to implement an integrated information system to support faster and more accurate decision making. The analysis was conducted using the SWOT method to identify the strengths, weaknesses, opportunities, and threats faced by the company. The results of the study indicate that the implementation of the right information system can optimize business processes from the office to the plantation. An integrated information system allows the company to manage inventory, production, and distribution data in real-time, thereby minimizing errors. This study also identified the need for human resource training for smooth system implementation. The use of cloud computing technology is recommended to improve data accessibility and support sustainable and measurable system integration. With recommendations for effective information system implementation, it is hoped that PT Pulau Subur can adapt to market changes and improve its overall operational performance.